2017
DOI: 10.1016/s2352-3018(17)30122-4
|View full text |Cite
|
Sign up to set email alerts
|

Progress of UNAIDS 90-90-90 targets in a district in KwaZulu-Natal, South Africa, with high HIV burden, in the HIPSS study: a household-based complex multilevel community survey

Abstract: Centers for Disease Control and Prevention and the US Presidents Emergency Plan for AIDS Relief (PEPFAR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 18 publications
9
65
2
Order By: Relevance
“…Current literature and analyses focus on gender differentials in health seeking behavior and linkage and retentionin the HIV care cascade in Southern Africa as a threat to achieving UNAIDS 90:90:90 targets [25, 26, 31]. Our findings further display the gender differential among newly-diagnosed PLHIV and ART initiation seen in similar studies [15, 20, 32].…”
Section: Discussionsupporting
confidence: 73%
“…Current literature and analyses focus on gender differentials in health seeking behavior and linkage and retentionin the HIV care cascade in Southern Africa as a threat to achieving UNAIDS 90:90:90 targets [25, 26, 31]. Our findings further display the gender differential among newly-diagnosed PLHIV and ART initiation seen in similar studies [15, 20, 32].…”
Section: Discussionsupporting
confidence: 73%
“…High income, less educated, and single groups were all less likely to be aware of their HIV status relative to low income, secondary educated and married persons respectively [26]. In South Africa, women were found to have more than two‐fold greater odds of Awareness of HIV‐Positive Status relative to men (95% CI 1.75 to 2.57) [27]. Furthermore, those aged 15 to 19 years had 0.16‐fold lower odds of Awareness of HIV‐Positive Status relative to those aged 45 to 49 years (95% CI 0.09 to 0.29).…”
Section: Resultsmentioning
confidence: 99%
“…We included 53 studies that reported data on ART Use , with six studies that produced statistical measures of association across demographic strata. Men were found to be more likely than women to use ART in Botswana while they were less likely to be on ART in Zambia; and no statistically significant association by gender was found in two South African studies [26,27,29,30]. Two studies found older age groups to be significantly more likely to be on ART compared to younger age groups [26,31], while two studies failed to find any association between age and ART Use [30,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations